Intracavity loss optimization in tunable dual-wavelength erbium-doped fiber laser - Al-Alimi A.W.; Al-Mansoori M.H.; Abas A.F.; Mahdi M.A.; Adikan F.R.M.; Ajiya M. (International Institute of Informatics and Cybernetics, IIIC, 2023)
A cost effective design of equal output power dual-wavelength laser is experimentally demonstrated. In this design, the two wavelength can be tuned simultaneously and cover 31.33 nm within C-band. Simultaneous equal power dual-wavelength laser are produced as the intracavity loss is optimized. We found that effective optimization is achieved by adjusting the cavity with lower loss. The power difference between the two wavelengths is less than 0.37 dB and flat within the tuning range.